REPRESENTASI ANARKISME DALAM FILM JOKER - Rachmad, Radinda Annisa; Amanda Gelgel, Ni Made Ras; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2021)
ABSTRACT The form of anarchism can be presented through films, such as the Joker film. The chaos of the city of Gotham arises because of the inequality of a corrupt city, resulting in a corrupt government and the birth of businessmen who can have any power to represent their interests, not the interests of the people of Gotham. The purpose of this research is to find out how anarchism is represented in the Joker film. This study uses a qualitative approach and is analyzed using the semiotic analysis of Charles Sanders Pierce. The related scenes in the film are analyzed using the Charles Sanders Pierce semiotic method which consists of sign, object and interpretant. The results of this study indicate that the Joker film represents anarchism in the form of threats and intimidation such as demonstrations, looting, riots and anarchism responses channeled through several media, support and thoughts of anarchism. Key Words :  Anarchism, Representation, Semiotics, Film